2007
DOI: 10.2337/dc06-2438
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, Parathyroid Hormone Levels, and the Prevalence of Metabolic Syndrome in Community-Dwelling Older Adults

Abstract: OBJECTIVE -Accumulating research suggests low-circulating vitamin D concentrations, i.e., 25-hydroxyvitamin-D [25(OH)D], may be associated with an increased prevalence of metabolic syndrome; however, previous studies have not accounted for parathyroid hormone (PTH) levels. We examined the association of 25(OH)D and PTH with the prevalence of metabolic syndrome in a community-based cohort of older adults. RESULTS -In men, there was a significant trend (P ϭ 0.03) of increasing adjusted odds for metabolic syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
283
11
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(321 citation statements)
references
References 47 publications
(47 reference statements)
25
283
11
2
Order By: Relevance
“…16 Interestingly, Asian Indians have been included in the category of 'metabolically obese normal weight' group, as they tend to have more disproportionately higher total body fat at any given BMI compared with those of the other ethnicities 7,17 that might also lead to a false characterization of individuals as vitamin D deficient, based on their serum estimates. We found a lack of association between serum 25-OH-D concentrations and MS. Our observations are in line with those of Reis et al, 18 who demonstrated lack of association between serum vitamin D levels and MS in adult Caucasian population from the southern California community of Rancho Bernardo. In the Longitudinal Aging Study conducted in old subjects in Amsterdam, Snijder et al 19 failed to find any association between diabetes and 25-OH vitamin D. Similarly, Scragg et al 6 observed no association between vitamin D status and type 2 diabetes in non-Hispanic blacks despite their poor vitamin D status and independent associations between 25-OH-D and risk of diabetes in other ethnicities (non-Hispanic whites and Mexican-Americans).…”
Section: Discussionsupporting
confidence: 93%
“…16 Interestingly, Asian Indians have been included in the category of 'metabolically obese normal weight' group, as they tend to have more disproportionately higher total body fat at any given BMI compared with those of the other ethnicities 7,17 that might also lead to a false characterization of individuals as vitamin D deficient, based on their serum estimates. We found a lack of association between serum 25-OH-D concentrations and MS. Our observations are in line with those of Reis et al, 18 who demonstrated lack of association between serum vitamin D levels and MS in adult Caucasian population from the southern California community of Rancho Bernardo. In the Longitudinal Aging Study conducted in old subjects in Amsterdam, Snijder et al 19 failed to find any association between diabetes and 25-OH vitamin D. Similarly, Scragg et al 6 observed no association between vitamin D status and type 2 diabetes in non-Hispanic blacks despite their poor vitamin D status and independent associations between 25-OH-D and risk of diabetes in other ethnicities (non-Hispanic whites and Mexican-Americans).…”
Section: Discussionsupporting
confidence: 93%
“…These findings are supported by results of some observational studies, 31,32 but not the others. 16,21,33 In the Longitudinal Ageing Study Amsterdam, serum PTH rather than serum 25OHD was associated with SBP or DBP, or prevalence of hypertension in 1205 men and women aged 65 years and older after adjustment of potential confounders.…”
Section: Discussionsupporting
confidence: 67%
“…[17] Other studies did not find such association. [18,19] This difference from our study can be explained on the basis of very large sample size and difference in ethnicity of the sample. One more study by Sheena et al had demonstrated independent associations of vitamin D with insulin sensitivity and beta-cell function in [21] as did Inzucchi et al in diabetic patients.…”
Section: Discussioncontrasting
confidence: 66%